PENGEMBANGAN MODEL PEMBELAJARAN LOMPAT JAUH MELALUI PERMAINAN LOMPAT BAMBU PADA SISWA KELAS V SD NEGERI 4 WULUNG KECAMATAN RANDUBLATUNG KABUPATEN BLORA TAHUN 2013 (Department of Physical Education, Sport, Health and Recreation, 2014)
The purpose of this research is to produce a product development model of learning through play jump longjump bamboo for elementary school students in the learning of Physical Education , Sport and Health.This research was carried out by means of two phases , namely a small scale using 10 students as researchsubjects and large -scale use of the subject 28 public elementary school students Wulung Randublatung 4 . Themethod of research is the development of a model refers to the development of Borg & Gall has been modified.The data analysis technique used is descriptive percentage to reveal aspects of psychomotor , cognitive andaffective student after using the product. From the test results that an expert evaluation of the data obtained ,the expert of physical education 98.67 % ( very mend ) , learning experts I 93.33 % (excellent ) , a second study86.67 % ( excellent ) , a small group of 86 trials , 6 % better ) , and a field test 90.9 % ( very good ). The results,of this study concluded that the model of learning through play jump long jump bamboo can be used by theteacher in the learning process for students long jump Elementary School 4 Wulung , Randublatung Blora .